2022
DOI: 10.1088/1741-2552/ac89b3
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive stimulation with temporal interference: optimization of the electric field deep in the brain with the use of a genetic algorithm

Abstract: Objective. Since the introduction of transcranial temporal interference stimulation (tTIS), there has been an ever-growing interest in this novel method, as it theoretically allows non-invasive stimulation of deep brain target regions. To date, attempts have been made to optimize the electrode montages and injected current to achieve personalized area targeting using two electrode pairs. Most of these methods use exhaustive search to find the best match, but faster and, at the same time, reliable solutions are… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Finally, we explored montage location based on an initial reference montage used for effective TI modulation in the deep brain. Future studies may adopt optimization studies to investigate optimized focality considering all scalp positions (Fernández-Corazza et al, 2020;Stoupis and Samaras, 2022). Also, TI and 2-tACS used the same montage location for fair comparison.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we explored montage location based on an initial reference montage used for effective TI modulation in the deep brain. Future studies may adopt optimization studies to investigate optimized focality considering all scalp positions (Fernández-Corazza et al, 2020;Stoupis and Samaras, 2022). Also, TI and 2-tACS used the same montage location for fair comparison.…”
Section: Discussionmentioning
confidence: 99%
“…This study revealed that TI electrical stimulation permitted more steerable and deeper stimulation than traditional tACS, suggesting that it might be used as an alternative or improved stimulation approach for tACS. Besides, a few studies also attempted to use more advanced algorithmic methods, such as artificial neural network (ANN) or genetic algorithm, to estimate the stimulation parameters of TI electrical stimulation, leading to more targeted stimulation on individual models (Karimi et al, 2019;Stoupis and Samaras, 2022).…”
Section: Optimal Parametersmentioning
confidence: 99%
“… Bahn et al (2023) developed an unsupervised neural network for simulating TI stimulation on the human brain that could rapidly and precisely optimize stimuli at deep brain targets. Moreover, Stoupis and Samaras (2022) discovered that using a genetic algorithm could drastically reduce the optimization time, making it possible to create personal stimulation plans rapidly. Research has indicated that unsupervised neural networks and genetic algorithms can be effective TI simulation algorithms.…”
Section: Simulation Studiesmentioning
confidence: 99%